Estratégias pedagógicas em uma turma de musicalização infantil inclusiva - Leticia Caroline Souza (2018)
This research aims to evaluate and delimitate pedagogical strategies pertinent to the context of inclusive musical education. Therefore, we have selected a group of 6 children, with ages ranging from 1 year and 6 months to 3 years, and their parents, that attended to an inclusive musical education program at Integrated Music Education Center at Federal University of Minas Gerais in 2017. The group was composed with 3 children with Down Syndrome and, 3, with typical development. 24 classes were hold on weekly base, with a duration of 30 minutes each. Grounded Theory was chosen as the methodological approach, allowing different data collecting tools such as video recording analyses of the classes along with other documents (teaching plan, reports etc.) and interviews with the parents, and triggering the following structure for this report: Part I Literature Review, comprising studies 1 and 2, both literature reviews, and Part II Field Study, comprising studies 3 and 4. Study 1 provided information about inclusive education in Brazil and its relationships with music classes in the contexts of regular education and specialized music school, while Study 2 emphasized the relationships between Down syndrome, Music Therapy and Music Education. Study 3 presented educational concepts from Vygotsky, Gainza, Orff, Schafer, Dalcroze, Parizzi and Sampaio, which became the guiding fundamental principles for the elaboration of the pedagogical plan and process of identification and elaboration of the pedagogical strategies applied in the classes. Study 4 has as its central element the evaluation of video clips from the classes, made by four invited judges trained in music education with experience in inclusive music education. They also answered a questionnaire to assist with data collection about their professional training, the relevance of strategies and their possible application in other educational contexts, among others themes. Subsequently, through quantitative analysis, the data collected were compared with those provided by the researcher. The results showed consistence and reliability between the judges and the researcher evaluations with the Kendall W of 0.675, and the alpha value higher than 0.88. We conclude that the list of pedagogical strategies is essential for children's music education, may serve as subsidies for professionals to reflect on their pedagogical practice and may be applied in other educational contexts. All materials can be used by other musical educators. Also, it was evidenced the relevance of the children´s music education for the potentialization of musical abilities and the overall development of the individuals.